Does using a chair backrest or reducing seated hip flexion influence trunk muscle activity and discomfort? A systematic review - Curran, M.; O'Sullivan, L.; O'Sullivan, Peter; Dankaerts, W.; O'Sullivan, K. (2015)
Objective: This paper systematically reviews the effect of chair backrests and reducing seated hip flexion on low back discomfort (LBD) and trunk muscle activation. Background: Prolonged sitting commonly exacerbates low back pain (LBP). Several modifications to seated posture and chair design have been recommended, including using chairs with backrests and chairs that reduce hip flexion. Method: Electronic databases were searched by two independent assessors. Part 1 of this review includes 26 studies comparing the effect of sitting with at least two different hip angles. In Part 2, seven studies that compared the effect of sitting with and without a backrest were eligible. Study quality was assessed using the PEDro scale. Results: Significant confounding variables and a relatively small number of randomized controlled trials (RCTs) involving people with LBP complicates analysis of the results. There was moderate evidence that chair backrests reduce paraspinal muscle activation, and limited evidence that chair backrests reduce LBD. There was no evidence that chairs involving less hip flexion reduce LBP or LBD, or consistently alter trunk muscle activation. However, participants in several studies subjectively preferred the modified chairs involving less hip flexion. Conclusion: The limited evidence to support the use of chairs involving less seated hip flexion, or the effect of a backrest, is consistent with the limited evidence that other isolated chair design features can reduce LBP. Application: LBP management is likely to require consideration of several factors in addition to sitting position. Larger RCTs involving people with LBP are required.